Compact triple‐band ground radiation antenna using two inner rectangular loops enclosed by two outer loops. Issue 10 (1st May 2016) - Qu, L.; Zhang, R.; Lee, H.; Kim, H.
Abstract : A triple‐band ground radiation antenna is proposed that can cover the 1575 MHz global positioning system (GPS) band and the 2.45 and 5.5 GHz WLAN bands, within a 6 × 9 mm ground clearance. The proposed triple‐band antenna is comprised of two inner rectangular loops, each enclosed by a larger outer loop. Each band can be adjusted for impedance matching by means of respective matching circuits. The −10 dB return loss bandwidths were simulated to be 17, 130 and 1000 MHz. Measurements indicated that sufficient bandwidth and good radiation performance were also achieved.